A blind channel shortening for multiuser, multicarrier CDMA system over multipath fading channel - F. Bouasria; A. Djebbari; M. Chetioui (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this paper we derive the Multicarrier Equalization by Restoration of Redundancy (MERRY) algorithm: A blind, adaptive channel shortening algorithm for updating a Time-domain Equalizer (TEQ) in a system employing MultiCarrier Code Division Multiple Access (MC-CDMA) modulation. We show that the MERRY algorithm applied to the MC-CDMA system converges considerably more rapidly than in the Orthogonal Frequency Division Multiplexing (OFDM) system [1]. Simulations results are provided to demonstrate the performance of the algorithm.